Driving Simulator, Virtual Reality, and On-Road Interventions for Driving-Related Anxiety: A Systematic Review. (3rd April 2021) - Knott, Melissa; Kim, Sang Ho; Vander Veen, April; Angeli, Erik; Evans, Eric; Knight, William; Ripley, April; Tran, Tuan; Alvarez, Liliana
Abstract: Driving-related anxiety contributes to negative changes in driving habits, skills, and satisfaction. Driving rehabilitation interventions have the potential to address driving-related anxiety, however, the evidence is not yet critically appraised. Researchers conducted a systematic review on the impact of on-road, driving simulator or virtual reality exposure therapy (VRET) driving rehabilitation interventions addressing driving-related anxiety. Searches in nine databases identified 1521 records, with 12 remaining for quality appraisal: two on-road, six driving simulator, and four on VRET. On-road interventions were low quality. Meanwhile, driving simulation and VRET interventions included high-quality evidence demonstrating significant reductions in psychological symptoms, subjective distress, and driving errors.